2017
DOI: 10.1074/jbc.m116.752402
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Counteracts Dopamine/PKA Signaling via Dephosphorylation of DARPP-32 Ser-97 and Alteration of Its Cytonuclear Distribution

Abstract: The interaction of glutamate and dopamine in the striatum is heavily dependent on signaling pathways that converge on the regulatory protein DARPP-32. The efficacy of dopamine/D1 receptor/PKA signaling is regulated by DARPP-32 phosphorylated at Thr-34 (the PKA site), a process that inhibits protein phosphatase 1 (PP1) and potentiates PKA action. Activation of dopamine/D1 receptor/PKA signaling also leads to dephosphorylation of DARPP-32 at Ser-97 (the CK2 site), leading to localization of phospho-Thr-34 DARPP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 41 publications
(91 reference statements)
0
24
0
Order By: Relevance
“…As it is known, there are multiple other neurotransmitters besides dopamine that regulate the excitability of dopaminoceptive neurons: glutamate, GABA, opiates, and adenosine, which are involved in signaling through DARPP-32 in MSNs [28]. In particular, in our previous studies the expression rates of catecholaminergic, glutamatergic and GABAergic receptors in the dorsal striatum were shown to be significantly altered as compared to the control group, in reverse directions for the defeated and aggressive mice [25,26].…”
Section: Glutamate Vs Dopamine Gradient In Msn Statesmentioning
confidence: 92%
See 1 more Smart Citation
“…As it is known, there are multiple other neurotransmitters besides dopamine that regulate the excitability of dopaminoceptive neurons: glutamate, GABA, opiates, and adenosine, which are involved in signaling through DARPP-32 in MSNs [28]. In particular, in our previous studies the expression rates of catecholaminergic, glutamatergic and GABAergic receptors in the dorsal striatum were shown to be significantly altered as compared to the control group, in reverse directions for the defeated and aggressive mice [25,26].…”
Section: Glutamate Vs Dopamine Gradient In Msn Statesmentioning
confidence: 92%
“…To gain fuller insight into the D1/D2 MSNs we retrieved the annotated genes implicated in PP1-regulated phosphorylation pathways in MSNs based on available literature [14,23,[27][28][29]. The compiled core gene set comprising cAMP-mediated dopamine response genes, expanded with NMDA glutamate receptor subunits Grina, Grin1-Grin2 and MAP kinases is presented in Table 1.…”
Section: Compilation Of Gene Setsmentioning
confidence: 99%
“…In vitro experiments on striatal neurons have recently revealed that dephosphorylation at the Thr34, Thr75, and Ser97 residues by PP2A/PR72 leads to nuclear accumulation of an inactive form of DARPP‐32 (Nishi et al . ). Thus, glutamate transmission may counteract dopamine D1 receptor signaling also through this mechanism.…”
Section: Dopamine and Darpp‐32 Signaling Pathwaysmentioning
confidence: 97%
“…Under basal conditions, DARPP‐32 is mainly phosphorylated at Thr75, Ser97, and Ser130 residues (Nishi et al . ) and acts as a PKA inhibitor (Fig. a).…”
Section: Dopamine and Darpp‐32 Signaling Pathwaysmentioning
confidence: 99%
“…The activation of dopaminergic and glutamatergic receptors regulates the phosphorylation of DARPP-32, but with opposite molecular mechanisms. Thus, the stimulation of dopamine D 1 receptor enhances the phosphorylation by PKA of Thr-34 site in DARPP-32 [Walaas et al, 1983;Walaas and Greengard, 1984], which acts as a strong PP1 inhibitor , whereas the activation of the NMDA receptor promotes the elevation of intracellular calcium, inducing dephosphorylation of DARPP-32 [Halpain et al, 1990;Nishi et al, 2005Nishi et al, , 2017 and reducing its PP1 inhibitory activity. In addition, DARPP-32 is phosphorylated/dephosphorylated by several other kinases and phosphatases with multiple cellular responses, including the regulation of cytonuclear trafficking and chromatin response [Johansen and Johansen, 2006;Stipanovich et al, 2008;Yger and Girault, 2011].…”
mentioning
confidence: 99%